Effects of Leader Narcissism on Career Success of Employees: An Interpersonal Relationship Perspective - Wang, Huaqiang; Li, Dan; Wu, Lei; Ding, Zhihui (Frontiers in Psychology, 2021)
Previous studies have shown that leader narcissism has a significant impact on the effectiveness of a leader and employee behaviors; however, research on career outcomes of employees is still inadequate. This study explores the effects of leader narcissism on the career success of employees from an interpersonal relationship perspective and examines the mediating role of supervisor-subordinate conflict and the moderating role of dominant personality traits of employees. Data from 291 employees in Chinese companies have revealed that leader narcissism, directly and indirectly, affects the career success of employees through supervisor-subordinate relationship conflict. However, dominant personality traits of employees strengthen the impact of leader narcissism on supervisor-subordinate relationship conflict. The theoretical and practical implications of the findings of this study are further discussed.